Floquet Theory for q-Difference Equations - Bohner, Martin; Chieochan, Rotchana (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce ω-periodic functions in quantum calculus and study the first-order linear q-difference vector equation for which its coefficient matrix function is ω-periodic and regressive. Based on the new definition of periodic functions, we establish Floquet theory in quantum calculus. 2000 Mathematics Subject Classification. 39A13, 34N05, 26E70